Pengaruh Penerapan Keselamatan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan Pada PT.Z - Della Ayu Minarni (Prosiding, 2025)
This research is motivated by the phenomenon of declining employee performance at PT. Z, accompanied by an increase in work accidents in the company, so that an in-depth analysis is needed regarding the relationship between the implementation of OHS and employee performance. The purpose of this study is to determine the effect of OHS implementation on employee performance in the manufacturing industry, as well as to provide strategic recommendations for company management in improving the effectiveness of the OHS program. The research method uses a quantitative approach with survey and interview techniques. The population in this study is all production employees, with a sample of 45 production employees of PT. Z determined through a saturated sampling method. The data collection instrument is a questionnaire that has been tested for validity and reliability, and analyzed using the Partial Least Square (PLS) method to examine the relationship between variables. The results show that the implementation of OHS has a positive and significant effect on employee performance. OHS indicators such as safe working conditions, OHS education and training, the creation of a healthy work environment have been proven to be able to improve work quality, work quantity, and work time. These findings indicate that the better the implementation of OHS, the higher the productivity and quality of work produced by employees. The conclusion of this study is that planned, consistent implementation of OHS, supported by management commitment, can be a determining factor in improving employee performance. Therefore, companies need to strengthen OHS policies through ongoing training programs, the provision of adequate safety facilities, and periodic evaluations to ensure the effectiveness of their implementation.